Disparate perspectives: Exploring healthcare professionals' misaligned mental models of older adults' transitions of care between the emergency department and skilled nursing facility. (October 2021) - Werner, Nicole E.; Rutkowski, Rachel A.; Krause, Sheryl; Barton, Hanna J.; Wust, Kathryn; Hoonakker, Peter; King, Barbara; Shah, Manish N.; Pulia, Michael S.; Brenny-Fitzpatrick, Maria; Smith, Maureen; Carayon, Pascale
Abstract: Care transitions that occur across healthcare system boundaries represent a unique challenge for maintaining high quality care and patient safety, as these systems are typically not aligned to perform the care transition process. We explored healthcare professionals' mental models of older adults' transitions between the emergency department (ED) and skilled nursing facility (SNF). We conducted a thematic analysis of interviews with ED and SNF healthcare professionals and identified three themes: 1) ED and SNF healthcare professionals had misaligned mental models regarding communication processes and tools used during care transitions, 2) ED and SNF healthcare professionals had misaligned mental models regarding healthcare system capability, and 3) Misalignments led to individual and organizational consequences. Overall, we found that SNF and ED healthcare professionals are part of the same process but have different perceptions of the process. Future work must take steps to redesign and realign these distinct work systems such that those involved conceptualize themselves as part of a joint process. Highlights: Care transitions across healthcare settings are a quality and safety challenge. Each healthcare setting performing transitions represents a distinct work system. Work systems are not aligned to perform care transitions for older adults. Healthcare professionals have misaligned mental models of transition processes. Misalignments led to individual and organizational consequences.